Overview of methods for characterization and visualization of a protein–protein interaction network in a multi-omics integration context - Robin, Vivian; Bodein, Antoine; Scott-Boyer, Marie-Pier; Leclercq, Mickaël; Périn, Olivier; Droit, Arnaud (Frontiers in Molecular Biosciences, 2022)
At the heart of the cellular machinery through the regulation of cellular functions, protein-protein interactions (PPI) have a significant role. PPI can be analysed with network approaches. Construction of a PPI network requires prediction of the interactions. All PPIs form a network. Different biases such as lack of data, recurrence of information and false interactions make the network unstable. Integrated strategies allow to solve these different challenges. These approaches have shown encouraging results for understanding of molecular mechanisms, drug action mechanism, identification of target genes. In order to give more importance to an interaction, it is evaluated by different confidence scores. These scores allow the filtration of the network and thus facilitate the representation of the network, essential steps to the identification and understanding of molecular mechanisms. In this review, we will discuss the main computational methods for predicting PPI, including ones confirming an interaction as well as the integration of PPI's into a network, and we will discuss of visualization of these complex data.